Microencapsulation improves chondrogenesis in vitro and cartilaginous matrix stability in vivo compared to bulk encapsulation. (29th January 2020) - Li, Fanyi; Levinson, Clara; Truong, Vinh X.; Laurent-Applegate, Lee Ann; Maniura-Weber, Katharina; Thissen, Helmut; Forsythe, John S.; Zenobi-Wong, Marcy; Frith, Jessica E.
Abstract : The encapsulation of cells into microgels is attractive for applications in tissue regeneration. Abstract : The encapsulation of cells into microgels is attractive for applications in tissue regeneration. While cells are protected against shear stress during injection, the assembly of microgels after injection into a tissue defect also forms a macroporous scaffold that allows effective nutrient transport throughout the construct. However, in most of current strategies that form microgel-based macroporous scaffold or higher-order structures, cells are seeded during or post the assembly process and not microencapsulated in situ . The objective of this study is to investigate the chondrogenic phenotype of microencapsulated fetal chondrocytes in a biocompatible, assembled microgel system vs . bulk gels and to test the stability of the constructs in vivo . Here, we demonstrate that cell microencapsulation leads to increased expression of cartilage-specific genes in a TGF-β1-dependent manner. This correlates, as shown by histological staining, with the ability of microencapsulated cells to deposit cartilaginous matrix after migrating to the surface of the microgels, while keeping a macroscopic granular morphology. Implantation of precultured scaffolds in a subcutaneous mouse model results in vessel infiltration in bulk gels but not in assembled microgels, suggesting a higher stability of the matrix produced by the cells in the assembled microgel constructs. The cells are able to remodel the microgels as demonstrated by the gradual disappearance of the granular structure in vivo . The biocompatible microencapsulation and microgel assembly system presented in this article therefore hold great promise as an injectable system for cartilage repair.